The Influence of Supervisors' Performance and Madrasah Principals' Leadership on The Quality of Inclusive Schools in the Era of Digital Transformation - Jumadi Jumadi; Abdul Rachman Sahrani; La Ode Amril; I Made Perdana Skolastika; Firman Muhammad Arif (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines the influence of supervisors’ performance and madrasah principals’ leadership on the quality of inclusive schools in the era of digital transformation. Although educational supervision and school leadership are widely recognized as determinants of school quality, empirical evidence regarding their integrated contribution to strengthening inclusive educational management remains limited. Methodology: This study employed a quantitative survey design involving all 16 teachers at Madrasah Aliyah Negeri in Bantaeng Regency, Indonesia, using a saturated sampling technique. Data were collected through a self-developed questionnaire that was validated by experts and demonstrated excellent reliability. Descriptive statistics, simple linear regression, and multiple linear regression analyses were conducted using IBM SPSS Statistics Version 25. Main Findings: The findings indicate that supervisors’ performance has a positive and significant influence on inclusive school quality, explaining 40.2% of the variance, while madrasah principals’ leadership explains 78.4%. Simultaneously, both variables explain 81.9% of the variance, indicating that their combined contribution provides greater explanatory power than either variable individually. These findings demonstrate that collaborative educational leadership strengthens teacher professionalism, organizational innovation, and inclusive educational practices in the digital transformation era. Novelty/Originality of this study: This study proposes the Collaborative Educational Leadership for Inclusive Madrasahs framework, integrating supervisors' performance and madrasah principals’ leadership into a unified model for improving inclusive school quality. The findings provide practical implications for policymakers and educational stakeholders to strengthen instructional supervision, transformational and digital leadership, and collaborative governance through continuous professional development to support sustainable inclusive education.